Basic Parameters and Characteristics of Seismicity in Mongolia - Klyuchevskii, AV; Bayart, G; Demjanovich, VM; Dungarmaa, T (Proceedings of the Mongolian Academy of Sciences, 2011)
Much of the territory of Mongolia is located in highly seismic areas of Central- Asian seismic belt and is subjected to frequent and large earthquakes. Its western half is particularly seismically dangerous. Only in twentieth century more than 60 earthquakes with M>5.5 (7 to 11-12 - intensity) occurred here, among which tens of earthquakes were responsible for severe destruction of the earth surface, and seismic disasters of 1905, 1931 and 1957 were accompanied by seismotectonic deformations to several hundred kilometers in length. Judging from the retained traces of ancient earthquakes and the chronicles, similar and probably larger seismic events occurred here in the recent past. DOI: http://dx.doi.org/10.5564/pmas.v0i4.39 Proceedings of the Mongolian Academy of Sciences 2007 No 4 pp.36-49